2011
DOI: 10.1002/anie.201007593
|View full text |Cite
|
Sign up to set email alerts
|

DNA as a Molecular Ruler: Interrogation of a Tandem SH2 Domain with Self‐Assembled, Bivalent DNA–Peptide Complexes

Abstract: Two peptides on display: The self‐assembly of DNA complexes enables the bivalent presentation of phosphopeptides. Flexibility and distance in the ligand arrangement can be adjusted through the choice of appropriate DNA templates. Spatial screening of the tandem SH2 domain of Syk kinase with these probes (see picture) indicated the accessible arrangements of the two homologous binding pockets and the flexibility of the connecting protein linker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 56 publications
2
75
0
Order By: Relevance
“…The nanoscaffold displayed the two domain-binding ligands at various distances and flexibilities. 44 …”
Section: Label-free Detection Of Bimolecular Interactionsmentioning
confidence: 99%
“…The nanoscaffold displayed the two domain-binding ligands at various distances and flexibilities. 44 …”
Section: Label-free Detection Of Bimolecular Interactionsmentioning
confidence: 99%
“…17,18 They also demonstrated that bivalent peptide-displayed duplexes with regular intervals as molecular rulers effectively bound to tandem SH2 domain of Syk kinase. 19 Moreover, Montesarchio and co-workers reported antiviral activity against HIV-1 of glycoconjugated DNA quadruplex. 20 Hamilton and co-workers constructed a pentaplex assembly of phosphocholine (PC)DNA conjugate in the presence of Cs + ions and revealed that the pentaplex assembly of PC binds to human C-reactive protein with 350-fold higher affinity than its monomeric counterpart.…”
Section: ¹1mentioning
confidence: 99%
“…2B). 15,32 Thermal denaturation analyses showed that the peptides had a negligible influence on the stability of the DNA duplexes ( Fig. S1 †).…”
Section: Spatial Screening Of the Recombinant α-Ear Domainmentioning
confidence: 99%